Audiology Research MDPI - (:unkn) unknown (My University, 2026)
Academic editors play a crucial role in leading our journals and ensuring that each article undergoes a robust and timely peer-review. With the launch of Topics this year and addition of Topic Editors to our family of academic editors, we decided it would be a good time to restructure our academic boards, thus providing more clarity and support for each role. MDPI is pleased to announce the launch of a new position—Topical Advisory Panel Member, that will replace the previous position of Topics Board Member. The Topical Advisory Panel will be comprised of early career researchers eager to gain experience in editorial work.